Estimation of burden of female breast cancer in India for the year 2016, 2021 and 2026 using disability adjusted life years - Kunnavil, Radhika; Thirthahalli, Chethana; Nooyi, Shalini Chandrashekar; Somanna, Shivaraj Nallur; Murthy, Nandagudi Srinivasa (International Journal Of Community Medicine And Public Health, 2017)
Background: Assessment of burden of breast cancer through DALYs would provide insights for formulating health policies and also for the evaluation of disease control programs. The main objective of the study is to estimate the burden of breast cancer in-terms of YLL, YLD (years of life lived with disability) and DALYs for breast cancer for the year 2016, 2021 and 2026 in India. Methods: The YLL, YLD and DALYs have been estimated by employing global burden of disease methodology using DISMOD. The published data on age, sex and breast cancer incidence and mortality for the years 2006-2008 relating to Population Based Cancer Registries under Indian Council of Medical Research, expectation of life for urban areas of country for 2006-2010, population of the country in 2011 and the projected population of the country during years 2016, 2021 and 2026 were utilized for computations. Results: Total DALYs were found to be 12, 44,773; 14, 10,192; 15, 72,071 in 2016, 2021and 2026 respectively showing an increase of 26.29% from 2016-2026 merely due to the increase in the size of the population and ageing. During the prime years of 30-59 years of age, the DALYs accounted for 76.3%, 75.5%, and 74.1% of total DALYs respectively from 2016-2026. Conclusion: It is estimated that total DALYs due to breast cancer in India would increase over the years. Hence, these computations reveal an urgent need for initiating primary & secondary prevention measures for the control of breast cancer in the country.